Simultaneous use of erythropoietin and LFM‐A13 as a new therapeutic approach for colorectal cancer. (25th January 2018) - Tankiewicz‐Kwedlo, Anna; Hermanowicz, Justyna Magdalena; Domaniewski, Tomasz; Pawlak, Krystyna; Rusak, Małgorzata; Pryczynicz, Anna; Surazynski, Arkadiusz; Kaminski, Tomasz; Kazberuk, Adam; Pawlak, Dariusz
Abstract : Background and Purpose: Bruton's tyrosine kinase (Btk) is a non‐receptor tyrosine kinase involved in the activation of signalling pathways responsible for cell maturation and viability. Btk has previously been reported to be overexpressed in colon cancers. This kind of cancer is often accompanied by anaemia, which is treated with an erythropoietin supplement. The goal of the present study was to assess the effects of combination therapy with erythropoietin β (Epo) and LFM‐A13 (Btk inhibitor) on colon cancer in in vitro and in vivo models. Experimental Approach: DLD‐1 and HT‐29 human colon adenocarcinoma cells were cultured with Epo and LFM‐A13. Cell number and viability, and mRNA and protein levels of Epo receptors, Btk and Akt were assessed. Nude mice were inoculated with adenocarcinoma cells and treated with Epo and LFM‐A13. Key Results: The combination of Epo and LFM‐A13 mostly exerted a synergistic inhibitory effect on colon cancer cell growth. The therapeutic scheme used effectively killed the cancer cells and attenuated the Btk signalling pathways. Epo + LFM‐A13 also prevented the normal process of microtubule assembly during mitosis by down‐regulating the expression of Polo‐like kinase 1. The combination of Epo and LFM‐A13 significantly reduced the growth rate of tumour cells, while it showed high safety profile, inducing no nephrotoxicity, hepatotoxicity or changes in the haematological parameters. Conclusion and Implications: Epo significantly enhances the antitumour activity of LFM‐A13, indicating that a combination of Epo and LFM‐A13 has potential as an effective therapeutic approach for patients with colorectal cancer.